2019
DOI: 10.3390/ijerph16040532
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity of Workers in a Hospital

Abstract: Purpose: This study aims to evaluate the physical activity of healthcare personnel and the affecting factors of physical activity (PA) in a hospital using an accelerometer device (Actigraph wGT3X-BT). Method: A total of 63 subjects (22 physicians, 19 nurses, and 23 supporting staff) participated and wore an accelerometer for seven days. Among the outputs, the mean counts for a minute, time spent for light, moderate, and vigorous intensity PA, and step count were extracted. As a secondary study, 16 subjects con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
1
10
0
2
Order By: Relevance
“…Despite the exploratory character of this study, we concluded that apprentices from the fields of nursing care and automotive mechatronics accumulate a considerable amount of physical activities over the course of a day. The findings point in the same direction as a recent study that included hospital workers [27], a population very similar to nursing apprentices. The registered values are outstanding in comparison to representative studies of the general population or adolescents of the same age [19] or studies examining other working populations that also used the ActiGraph (e.g., [28]).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Despite the exploratory character of this study, we concluded that apprentices from the fields of nursing care and automotive mechatronics accumulate a considerable amount of physical activities over the course of a day. The findings point in the same direction as a recent study that included hospital workers [27], a population very similar to nursing apprentices. The registered values are outstanding in comparison to representative studies of the general population or adolescents of the same age [19] or studies examining other working populations that also used the ActiGraph (e.g., [28]).…”
Section: Discussionsupporting
confidence: 83%
“…In this context, the role of specific working positions such as "overhead" work has been highlighted due to its considerable risk of physical impairment [32,33]. Likewise, nurses are required to walk around in order to move medical equipment and care for patients through handling or transferring them, so that they have to face intensive physical tasks within their job [27,34].…”
Section: Discussionmentioning
confidence: 99%
“…The information collected included age, sex, number of family dependents, part‐time or full‐time working, frequency of night shift working, and general health status. These factors were selected based on a literature review (Wilkerson, Thomas, & Nahar, 2019) and the research results (Jun et al., 2019; McCarthy, Wills, & Crowley, 2018) with regard to socio‐demographic factors associated with physical activity.…”
Section: Methodsmentioning
confidence: 99%
“…(27) Um estudo realizado em um hospital universitário nos EUA com diferentes profissionais, encontrou que os enfermeiros possuem um nível satisfatório de AF durante a jornada de trabalho, sugerindo que a intensidade física das tarefas do hospital é alta. (28) Entretanto, tais exigências físicas podem estar relacionadas a distúrbios osteomusculares em enfermeiros, com aumento significativo de risco quando associados à falta de AF. (29) Também foi observado que quanto maior a quantidade de locais anatômicos com sintomas musculoesqueléticos, pior a qualidade de vida de profissionais de enfermagem.…”
Section: Discussionunclassified